Qualidade física de um latossolo sob plantio direto submetido à escarificação de sítio específico e o rendimento da soja - Girardello, Vitor Cauduro (2010)
The soil compaction has been noted under no-till especially in clay soil texture. One important characteristic of soil compaction in cropland is non-uniform occurrence. With precision farming (PF) is possible determine spatially the soil compaction allowing the site specific management defined as site specific chisel (SSC). This work was carried out in a cropland managed with PF in Victor Graeff, RS. The soil is Red Latossol with Cfa climate following Koppen classification. The treatments were: a) conventional chisel tillage (CCT); b) site specific chisel with uniform depth (SSCU); c) site specific chisel with variable depth (SSCV) and d) check plot - non disturbed soil (NC). The main evaluations were: water infiltration and other soil physic characteristics: macroporosity, microporosity, total porosity, relative density and aggregate stability soil layers: 00-0.05, 0.05 0.1, 0,1 0.15 e 0.15 -0.20 m , yield map, soil cover, soil resistance assessed by penetrometer, fuel consumption. The soil resistance indicated the soil compaction occurrence in zones of the cropland. The chisel tillage improved the soil physic characteristics, but it didn t improve the soybean yield. Besides that, the infiltration rate was increased five times, but after seven months the infiltration rate decreased 70%. The site specific chisel maintains 70% of soil cover, while conventional chisel only 25%. It was found high relationship between soil resistance and soybean yield (r2=0.87) and soil resistance and temporal yield variability (r2=0.97).